Dari Hutan Produksi ke Kawasan Konservasi: Kajian Tentang Kawasan Gunung Ciremai Tahun 1978-2014 - Tety Fajrul 'Aini; S. Nawiyanto (Program Studi Ilmu Sejarah Fakultas Ilmu Budaya Universitas Jember, 2021)
ABSTRACT This study examines the dynamics of changing forest status in the Mount Ciremai area which has undergone several changes for the sake of an interest. The Mount Ciremai area was first designated as a protected forest during the reign of the Dutch East Indies, and was designated as a production forest in 1978, until it was designated a conservation area in 2014. The problem that is examined in this study is the conditions of the initial area of ​​the Mount Ciremai area before it was designated as forest. production, the factors behind the change in the status of the forest in the Mount Ciremai area from a production forest to a conservation area, and the influence of the Mount Ciremai area on the surrounding community as a forest buffer zone. The author studies it with an ecological approach and used the historical method according to Kuntowijoyo. The method include the stages of topic selection, source collection, verification, interpretation and writing or historiography. Before becoming a production forest, the Mount Ciremai area was a protected forest established by the Dutch East Indies Government in 1941. Natural Resources in the Mount Ciremai area were of concern because they form forests that are dominated by pine species. In 1978, the Gunung Ciremai area was designated as a production forest for approximately twenty-six years. The ongoing forest production activity for a long time has caused the forest in the Mount Ciremai area to experience a decline. This has made the Mount Ciremai area converted into a National Park. The appointment was made in 2004 and set in 2014. The change of status to a national park is an attempt by the government to save forests from excessive damage. The conservation regulations that are enacted have an impact on the environment, social and economy of the people living around the forest. Keywords: Conservation, Mount Ciremai, Flora, Fauna, National Park.